Indigenous parents and child welfare: Mistrust, epistemic injustice, and training - Leckey, Robert; Schmieder-Gropen, Raphael; Nnebe, Chukwubuikem; Clouthier, Miriam (Social & Legal Studies, 2022)
The settler state's taking of Indigenous children into care disrupts their communities and continues destructive, assimilationist policies. This article presents the perceptions of lawyers, social workers and judges of how Indigenous parents experience child welfare in Quebec. Our participants characterized those experiences negatively. Barriers of language and culture as well as mistrust impede meaningful participation. Parents experience epistemic injustice, wronged in their capacity as knowers. Mistrust also hampers efforts to include Indigenous workers in the system. Emphasizing state workers’ ignorance of Indigenous family practices and the harms of settler colonialism, participants called for greater training. But critical literature on professional education signals the limits of such training to change institutions. Our findings reinforce the jurisdictional calls away from improving the system towards empowering Indigenous peoples to run services of child welfare. The patterns detected and theoretical resources used are relevant to researchers of other institutions that interact with vulnerable populations.
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; approches et analyses; australie; canada; care; cours; cycles supérieurs; discipline; droit; enfants autochtones; fem9000; injustice; inégalités; nouvelle-zélande; océanie; politique assimilationniste; périodes historiques; racisme; régions géographiques; santé; science politique et droit; sciences humaines; sciences sociales; système colonial; systèmes d'oppressions; thématiques; violences; états coloniaux

Conférence: «Droit et féminisme - Rencontre entre deux champs» - Institut de recherches et d'études féministes; Réseau Québécois en études féministes (2018)
Avec Rachel Chagnon, membre de l'Institut de recherches et d'études féministes et professeure au Département des sciences juridiques.
Keywords: amériques; approches et analyses; discipline; discours dominant; droit; droits des femmes*; europe; féminisme décolonial; histoire du féminisme; intersectionnalité; inégalités; militance; mouvements des femmes*; rapports sociaux de sexe; ressource en ligne; régions géographiques; science politique et droit; sciences humaines; sciences juridiques; sociologie; système colonial; systèmes d'oppressions; thématiques

Les oubliés du Code civil du Québec - Caron, Vincent; Berthold, Gabriel-Arnaud; Deslauriers-Goulet, Charlotte; Torres-Ceyte, Jérémie; LeBel, Louis (Les Éditions Thémis, 2014)
À l’occasion du vingtième anniversaire de l’entrée en vigueur du Code civil du Québec – événement symbolique d’importance – , il est apparu opportun d’amorcer une réflexion sur « les oubliés du Code civil », c’est-à-dire des notions qui évoluent en marge de l’œuvre codificatrice. Cet ouvrage a pour objet de faire la lumière sur certaines de ces notions dans une perspective dynamique. Ainsi, autour des principales divisions du Code civil – le droit des personnes, le droit de la famille, le droit des biens et le droit des obligations -, les auteurs offrent leurs réflexions et nourrissent un débat fertile et salutaire sur l’évolution du droit civil au Québec. Préface de Louis LeBel, juge à la Cour suprême du Canada de 2000 à 2014.
Section: xix, 226 pages ; 23 cm
Keywords: LGBTQIA2+; amériques; approches et analyses; canada; cours; discipline; droit; histoire et politique; inégalités; justice sociale; premier cycle; québec; régions géographiques; science politique et droit; soc2014; systèmes d'oppressions; thématiques

« Quelque longue que soit l’absence » : procurations et pouvoir féminin à Québec au xviiie siècle - Grenier, Benoît; Ferland, Catherine (Clio. Femmes, Genre, Histoire, 2013)
Dans les sociétés préindustrielles, l’exercice du pouvoir au sein de la famille est étroitement lié aux contingences juridiques et aux normes patriarcales. La connaissance du rôle joué par les femmes dans les activités économiques de la famille, en particulier les femmes mariées, échappe le plus souvent aux historiens. L’étude des procuratrices à Québec, capitale de la Nouvelle-France au xviiie siècle, permet de mieux comprendre le fonctionnement du couple dans un contexte colonial marqué par l’absentéisme masculin. L’analyse des actes de procurations octroyés aux femmes, combinée à une étude prosopographique de nature sociodémographique, révèle les enjeux et les circonstances de ce transfert circonstanciel de pouvoir. Cette voie montre qu’il est possible de contourner partiellement le silence entourant les activités des épouses pour éclairer la délicate question de la complémentarité et de la confiance au sein du couple.
ISBN: 9782701177816 Number: 37 Publisher: Éditions Belin https://journals.openedition.org/clio/11053
Keywords: 1600-1699; 1700-1799; amérique du nord; amériques; approches et analyses; canada; cours; discipline; droit; droit des femmes*; his4523; histoire; histoire des femmes*; histoire et politique; inégalités; mariage; maternité; patriarcat; premier cycle; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; science politique et droit; sciences humaines; sexisme; systèmes d'oppressions; thématiques

Law Reform, Lesbian Parenting, and the Reflective Claim - Leckey, Robert (Social & Legal Studies, 2011)
The article aims to complicate efforts to make law fit or catch up to social practices. It scrutinizes the ‘reflective claim’ using the case study of recognition of parenting by lesbian couples. Reforms in the United Kingdom’s Human Embryology and Fertilisation Act 2008 and the Canadian province of Quebec’s civil code are compared with empirical work from the social sciences on lesbians’ family practices. The reflective claim rests on problematic ideas about social practices and law. Since law is always blunt and incomplete, choices must be made as to which practices it should aim to recognize. Furthermore, the impact of heterosexist and homophobic conditions on lesbian families means that observable practices may not be a suitable model for gay-affirmative reforms. As advanced in the literature, the reflective claim overlooks law and society’s complex interaction, including how reform will not merely reflect but also alter practices. It fails to do justice to law reform’s normative character, obscuring its costs and positive potential
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amérique du nord; amériques; angleterre; approches et analyses; canada; corps; cours; discipline; discours dominant; droit; droit des femmes*; europe; hétérosexisme; identités LGBTQIA2+; inégalités; maternité; parentalité; premier cycle; périodes historiques; queer; québec; régions géographiques; science politique et droit; sciences humaines; soc2264; sociologie; systèmes d'oppressions; thématiques

Decoding Black Women: Policing Practices and Rape Prosecution on the Streets of Philadelphia - Irving, Toni (NWSA Journal, 2008)
Black women are generally displaced as victims of rape. The police response to the sexual assault of black women in general and lower-class black women in particular is illustrative of how sexual ideologies help construct complex social hierarchies that in turn structure rights. How the law currently deals with rape places black women outside of the narrative frames that legitimate entitlement. Rape continues to stand in for, and effectively obscure, other social, political, and economic concerns. Unpublished and often ignored, the rape narrative is a ripe site to supply oppositional interpretations of national experience and transmit some of the structural problems in the criminal justice system. Pulling from over two thousand “real” rape cases of low-income black women ignored and not investigated in Philadelphia between 1995 and 2000, this article reads black female rape narratives as case studies in order to discuss the way personal narratives of rape victims are structured by competing and overwhelming sociolegal narratives that undercut their reception. As the fastest growing prison population, the presence of the law to punish black women stands in stark contrast to the absence of the law to protect them.
Keywords: 1900-1999; 1990-1999; afro-féminisme; amériques; approches et analyses; arts; corps; cours; discipline; droit; droit des femmes* noires; droits des femmes*; féminisme afroaméricain; histoire et politique; intersectionnalité; inégalités; philadelphie; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; science politique; science politique et droit; sex2283; sexisme; systèmes d'oppressions; thématiques; viol; violences; états-unis; études littéraires